2016
DOI: 10.1139/cjm-2015-0466
|View full text |Cite
|
Sign up to set email alerts
|

Potential pathogenicity ofAeromonas hydrophilacomplex strains isolated from clinical, food, and environmental sources

Abstract: Aeromonas are autochthonous inhabitants of aquatic environments, including chlorinated and polluted waters, although they can also be isolated from a wide variety of environmental and clinical sources. They cause infections in vertebrates and invertebrates and are considered to be an emerging pathogen in humans, producing intestinal and extra-intestinal diseases. Most of the clinical isolates correspond to A. hydrophila, A. caviae, and A. veronii bv. Sobria, which are described as the causative agents of wound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…A pair of primer gyrB-F: 5 -GAAGTCATCATGACCGTTCTGCA(TC)GC(TCAG)GG(TCA G)GG(TCAG)AA(AG)TT(TC)GA-3 and gyrB-R: 5 -AGCAGGGTACGGATGTGCGAGCC(AG)TC(TCAG)AC(AG) TC(TCAG)GC(AG)TC(TCAG)GTCAT-3 (Yamamoto and Harayama, 1995) was used for amplification of the gyrB gene. PCR amplification was performed using a Biometra TProfessional Thermocycler (TaKaRa, Japan) according to a previous report (Albarral et al, 2016). The amplified products were observed and then sequenced at Sangon (Shanghai, China).…”
Section: S Rrna and Gyrb Gene Sequences Analysismentioning
confidence: 99%
“…A pair of primer gyrB-F: 5 -GAAGTCATCATGACCGTTCTGCA(TC)GC(TCAG)GG(TCA G)GG(TCAG)AA(AG)TT(TC)GA-3 and gyrB-R: 5 -AGCAGGGTACGGATGTGCGAGCC(AG)TC(TCAG)AC(AG) TC(TCAG)GC(AG)TC(TCAG)GTCAT-3 (Yamamoto and Harayama, 1995) was used for amplification of the gyrB gene. PCR amplification was performed using a Biometra TProfessional Thermocycler (TaKaRa, Japan) according to a previous report (Albarral et al, 2016). The amplified products were observed and then sequenced at Sangon (Shanghai, China).…”
Section: S Rrna and Gyrb Gene Sequences Analysismentioning
confidence: 99%
“…The expression of hemolysins has infrequently been assessed in bacterial isolates from environmental samples (Bevivino et al 2002;González-Rodríguez et al 2007;Albarral et al 2016) and much less is known about the hemolytic activity of Arctic species. As warming global temperatures are favoring the geographic expansion of pathogens and increasing the risk of human exposure to infectious disease (Revich et al 2012;IPCC 2014), it is increasingly important to study the presence of potential pathogens in Arctic environments and the expression of virulent phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial biofilm formation is a complicated multifaceted mechanism, associated with attachment, quorum sensing, cell wall synthesis, metabolism, and stress response [32]. The increasing antimicrobial resistance and virulence of bacterial species are due to their ability to produce biofilms [7]. All the isolates from our study are strong biofilm producers.…”
Section: Discussionmentioning
confidence: 81%
“…The pathogenic virulence factors of A. hydrophila include adhesions, cytotoxins, hemolysins, and proteases, and are able to form biofilms and alter gene expression and metabolic pathways under various host environments [5] [6]. Over the years, research on A. hydrophila has shown that they stick to hard exteriors and establish biofilms on the glass exteriors, polystyrene, polyvinyl chloride, and stainless steel [7]. Biofilms are considered as the leading root of perpetual infection and drug resistance, largely because of their ability to align with the visceral organs and other material surfaces [8].…”
Section: Introductionmentioning
confidence: 99%